Making sense of religion: a qualitative inquiry into students’ conceptions of religion in two Chinese regions - Zhao, Zhenzhou (British Journal of religious education, 2021)
The way religion is taught in Chinese schools is drawing attention, as challenges arise associated with the resurgence of various religious traditions in contemporary Chinese society. Existing research has revealed that the decades-long institutional separation of religion and education in China has had a complex effect on Chinese students’ understanding of religion. Efforts have been made to understand how Chinese textbooks present religion, but little is known about how students form their own perspectives on religion. Drawing on data collected in two geographical regions of China, this study explores how students conceive the meaning and role of religion. The findings reveal several key themes in the students’ understanding of religion, on topics including the association of religion with superstition, the relationship between religion and science, and the role of religion in modern society. The findings also have implications for how the Chinese school curriculum might be reformed in regard to the teaching of religion.